Peran Media Sosial Instagram @Abouttng Dalam Membangun Interaksi Sosial Masyarakat Tangerang - Aisyah Putri Nurhidayah; Dhea Meisyah Rani; Widya Nurhaliza; Adil Muhamad Zein (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to investigate the role of the social media platform Instagram @abouttng in fostering social interaction among the community in Tangerang. Additionally, the study explores the types of content utilized to enhance interaction on this platform. A mixed-methods research approach was employed, involving surveys, interviews, and content analysis. Surveys were conducted to gather data on the frequency of Instagram @abouttng usage, interaction patterns, and users' perceptions of its impact on social relationships. In-depth interviews were conducted with a selection of social media users to gain insights into their personal experiences and interaction strategies. Content analysis was performed to identify the most effective types of content in building social interaction. Demographic and cultural factors were also considered in the analysis. The findings of this study are expected to provide a better understanding of the role of social media in shaping local community social interactions and insights for the development of more effective digital communication strategies.